2022
DOI: 10.13057/biodiv/d230209
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, occurrence and molecular characterization of Bacillus related species isolated from different soil in Basrah Province, Iraq

Abstract: Abstract. Alyousif NA. 2021. Distribution, occurrence and molecular characterization of Bacillus related species isolated from different soil in Basrah Province, Iraq. Biodiversitas 23: 679-686. Bacillus related species are widely predominant in various environments such as soil with diverse environmental conditions. These bacteria are one of the most explored groups of bacteria in industrial biotechnology due to their enzymes. The present study was aimed to isolate, screen and determine the distribution of Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…As a spore-forming and Gram-positive organism, it can survive under many conditions in the environment and colonize a range of environments including saline soils (Song et al, 2017). The other organism identified as Cytobacillus species which is related to the Bacillus genus are commonly found in the soil as well (Wei et al, 2016;Alyousif, 2022). Previously known as Bacillus Firmus, several pieces of evidence have shown that this organism is distinct from members of the Bacillus genus and can survive in the soil for long periods, and has been reported from many types of soils (Patel and Gupta, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a spore-forming and Gram-positive organism, it can survive under many conditions in the environment and colonize a range of environments including saline soils (Song et al, 2017). The other organism identified as Cytobacillus species which is related to the Bacillus genus are commonly found in the soil as well (Wei et al, 2016;Alyousif, 2022). Previously known as Bacillus Firmus, several pieces of evidence have shown that this organism is distinct from members of the Bacillus genus and can survive in the soil for long periods, and has been reported from many types of soils (Patel and Gupta, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial diversity particularly in genetic diversity still is an undergoing aspect of current research from bacteria, archaea fungi, and the microbial origin from the rhizosphere, phyllosphere, soil, and plant pathogens. For example, the total Bacillus related bacterial species were investigated from different soil environments (Alyousif 2022). Among them, the BOX fingerprint technique was applied to soybean phyllosphere bacteria diversity (Nurcahyanti et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus is a big and diversified genus of rod-shaped, Gram-positive, endospore-forming bacteria that are aerobic and facultatively anaerobic, and they are a genus of the Bacillaceae family that belongs to the Firmicutes phylum (Errington and van der Aa 2020). In fact, it appears that the physiological aspects of Bacillus genus members have enabled them to inhabit almost all natural environment, such as water, air, soil, lake sediments, and fodder, and also harsh environments including thermal acid water, salt marshes, and hot springs (Gopal et al 2015;Alyousif 2022). The survival of Bacillus genus members for a long time in various extreme conditions is due to the formation of protective endospores that withstand unfavorable environmental conditions (Zammuto et al 2020).…”
Section: Bacterial Identification By 16s Rdnamentioning
confidence: 99%